2014
DOI: 10.1111/gbi.12093
|View full text |Cite
|
Sign up to set email alerts
|

The isotopic biosignatures of photo‐ vs. thiotrophic bivalves: are they preserved in fossil shells?

Abstract: Symbiont-bearing and non-symbiotic marine bivalves were used as model organisms to establish biosignatures for the detection of distinctive symbioses in ancient bivalves. For this purpose, the isotopic composition of lipids (δ13C) and bulk organic shell matrix (δ13C, δ34S, δ15N) from shells of several thiotrophic, phototrophic, or non-symbiotic bivalves were compared (phototrophic: Fragum fragum, Fragum unedo, Tridacna maxima; thiotrophic: Codakia tigerina, Fimbria fimbriata, Anodontia sp.; non-symbiotic: Tape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 98 publications
(109 reference statements)
0
12
1
Order By: Relevance
“…In a recent study, Dreier et al . () suggested that bulk organic shell matrices in Recent phototrophic and thiotrophic bivalves have lower δ 13 C org values (ranging from −31.0‰ to −25.5‰) than those of filter‐feeding non‐symbiotic bivalves where the latter have δ 13 C org values from −22.0‰ to −17.8‰. Comparable δ 15 N org values are −2.2‰ to +0.1‰ for thiotrophic bivalves, +2.6‰ to +2.9‰ for phototrophic bivalves and +3.1‰ to +4.3‰ for filter‐feeders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Dreier et al . () suggested that bulk organic shell matrices in Recent phototrophic and thiotrophic bivalves have lower δ 13 C org values (ranging from −31.0‰ to −25.5‰) than those of filter‐feeding non‐symbiotic bivalves where the latter have δ 13 C org values from −22.0‰ to −17.8‰. Comparable δ 15 N org values are −2.2‰ to +0.1‰ for thiotrophic bivalves, +2.6‰ to +2.9‰ for phototrophic bivalves and +3.1‰ to +4.3‰ for filter‐feeders.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation of the δ 13 C org and δ 15 N org values (Dreier et al . , fig. 1) suggests that the chemosymbiotic lifestyle is characterized by low δ 13 C org /low δ 15 N org , the non‐symbiotic lifestyle by high δ 13 C org /high δ 15 N org and the phototrophic lifestyle by low δ 13 C org /intermediate δ 15 N org .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently known Fraginae-associated symbiont phylogenetic diversity based on our results and five other molecular studies (Carlos et al, 1999(Carlos et al, , 2000Baillie et al, 2000;LaJeunesse, 2001;Dreier et al, 2014) are summarized ( Table 3, Supplementary Table 2). All freshly isolated symbiont communities (i.e., non-cultured) were from clade C, except for one individual of Fragum unedo, which harbored clade A symbionts .…”
Section: Phylogenetic Position Of Fraginae Symbiontsmentioning
confidence: 93%
“…Their symbionts are mostly placed into Symbiodinium clade A, C, and occasionally D (Kirkendale and Paulay, 2017; see comprehensive literature list in Supplementary Table 2) and a single host individual can sometimes possess multiple symbiont lineages (DeBoer et al, 2012). Within Fraginae, the symbiont community from four species have been examined to date using molecular markers: Fragum fragum (Linnaeus, 1758), Fragum unedo (Linnaeus, 1758), Corculum cardissa, and Corculum monstrosum (Gmelin, 1791) (Carlos et al, 1999(Carlos et al, , 2000Baillie et al, 2000;LaJeunesse, 2001;Dreier et al, 2014). Symbionts freshly isolated from the hosts mostly belong to Symbiodinium clade C, while symbionts cultured from host tissues are from clade A (Carlos et al, 1999).…”
Section: Introductionmentioning
confidence: 99%